Concept and Implications of Legislative Theory in Omnibus Law - Utami, Tanti; Shifa, Agisni; Oktaviani, Mita; Amanda, Shakilla; Madinawati, Shifa (Indonesian Journal Publisher, 2025)
This research to analyze the implementation of the omnibus law concept within Indonesia’s legal system using legislative theory as a framework for evaluation. It focuses on assessing the feasibility, impact, and long-term implications of adopting a legislative method commonly found in common law countries and applying it in a nation that adheres to the civil law tradition. The research adopts a normative juridical method with a literature-based approach, collecting data from academic books, journals, articles, statutory regulations, and judicial decisions relevant to legal development and regulatory reform in Indonesia’s current context. The study finds that the omnibus law has the potential to simplify the legal framework, eliminate overlapping regulations, and increase economic competitiveness through more efficient governance and legal certainty. However, the research also uncovers critical legal and constitutional issues, such as inconsistencies with the principle of the single subject rule, ambiguity in the legislative hierarchy, and a lack of substantive public participation. The findings emphasize that the current legal structure, as outlined in Law No. 12 of 2011 and its amendment, is not adequately equipped to support the comprehensive nature of omnibus legislation. Therefore, for this concept to be properly implemented, it must be accompanied by institutional and procedural reforms, including legal amendments, mechanisms for transparent harmonization, and inclusive civic engagement. These adjustments are essential to ensure the legitimacy, legal certainty, and democratic accountability of laws made under the omnibus model. Ultimately, without these fundamental reforms, the omnibus law risks undermining the very legal order it seeks to streamline.